Debate teórico sobre la televisión pública: un análisis de TV Brasil y Televisión Pública (Argentina) [Miscelánea] - Pereira Noleto, Amanda Lais (2025)
The dialogue about television—and public television, in particular—also entails reflecting on the possibilities for democratization that this space offers for the democratization of customs and political culture. In this context, public broadcasters emerge, consolidating their position as media outlets linked to the general interest through a communication project aimed at the public sphere. Based on these reflections, this article proposes a theoretical debate on public television in Brazil and Argentina through an analysis of TV Brasil and Argentine public television. It should be noted that this study is the result of ongoing doctoral research, and among the main findings obtained from a bibliographical study and a comparative journalism study, it can be affirmed that the two countries share a similarity in the historical context of the emergence of public television, in addition to the urgent need to study this type of television—and its programming—in order to understand the context of these stations in both countries.